Miniscrew implants for intrusion of supraerupted molar: A noninvasive approach for space regaining - Adrita Purkayastha; Rinkee Mohanty; Sourav Panda; Utkalika Das (Wolters Kluwer Medknow Publications, 2019)
Inadequate interocclusal space often leads to difficulty in prosthetic rehabilitation. Dental implant-indicated sites are governed by various factors which include bone availability, adequate mesiodistal width, and most importantly, adequate interocclusal space for proper prosthetic design on the dental implant. The use of miniscrew implant with coil spring for regaining interocclusal space would be an advantageous procedure for biomechanical intrusion of supraerupted teeth, rather than treating the same with invasive clinical crown reduction/intentional endodontic treatment. This case report describes the use of miniscrew implant with coiled spring on a supraerupted maxillary molar for interocclusal space regaining, to facilitate proper prosthetic rehabilitation in the dental implant site.